2017
DOI: 10.1039/c6ta09122a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin MoS2–MoO3 nanosheets functionalized CdS photoanodes for effective charge transfer in photoelectrochemical (PEC) cells

Abstract: The study focuses on hydrothermal synthesis of MoS2–MoO3 nanostructures and their application in the modification of CdS photoanodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Yuan et al developed a 2D–2D nanojunction between MoS 2 and TiO 2 and tested the photocatalytic water reduction reaction. 9a A number of studies have been reported for enhancing the photocatalytic performance due to heterojunctions such as n -BiVO 4 -MoS 2 , 11 MoS 2 -MoO 3 /CdS, 12 MoS 2 /CdS, 13 and MoS 2 /N-RGO/CdS. 14…”
Section: Introductionmentioning
confidence: 99%
“…Yuan et al developed a 2D–2D nanojunction between MoS 2 and TiO 2 and tested the photocatalytic water reduction reaction. 9a A number of studies have been reported for enhancing the photocatalytic performance due to heterojunctions such as n -BiVO 4 -MoS 2 , 11 MoS 2 -MoO 3 /CdS, 12 MoS 2 /CdS, 13 and MoS 2 /N-RGO/CdS. 14…”
Section: Introductionmentioning
confidence: 99%
“…The peaks positioned at 900-600 and 400-200 cm In order to further confirm the crystal structure of MoS 2 after KI/I 2 solution treatment, XRD analysis was conducted [33,34]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17] Beyond the photocatalytic lms, the conductive substrate is the other key part of the PEC electrode, and the materials of which are normally TCOs. [18][19][20][21] For a typical photoanode, TCO lms normally bind the photocatalytic lms and the substrate support to collect photoexcited electrons, which are then transferred to the cathode on the other side for the reductive reaction. 22,23 Typical TCOs include uorine/indium doped tin oxide (FTO/ITO) and aluminum doped zinc oxide (AZO), which are already commercialized by coating at lms on glass or polymer substrates.…”
Section: Introductionmentioning
confidence: 99%